Fenomena Pemberitaan Media Indonesia dalam Konflik Senjata Kimia di Ghouta Timur (Berdasarkan Perspektif Edmund Husserl) - Muhammad Naufal Annabil (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2021)
This article aims to describe the chemical weapons conflicts in Ghouta East, Syria based on the perspective of Edmund Husserl. The problems to be studied are the chemical weapons conflict in East Ghouta; the impact of chemical weapons use, and media in Indonesia's view of the chemical weapons conflict in East Ghouta through the line of phenomenology theory of Edmund Husserl. The research method used is the qualitative method. Data collection is used with watching, seeing, reading, and note techniques. The data analysis technique used is the descriptive analysis technique. To examine the validity of data, the technique used is the triangulation technique. As for the result of this research is the armed conflict occurred because of the opposition in East Ghouta and Assad's regime with its soldiers trying to eradicate the opposition; chemical weapons caused many injured victims to die, especially children; a dispute between the Western media and the Indonesian media in the news of the conflict in East Ghouta.Keywords - phenomenology, Indonesian media, chemical weapon, East Ghouta, Edmund Husserl